Speech prosody in cerebellar ataxia. - Casper, Maureen A.; Raphael, Lawrence J.; Harris, Katherine S.; Geibel, Jennifer M. (International Journal of Language & Communication Disorders)
Persons with cerebellar ataxia exhibit changes in physical coordination and speech and voice production. Previously, these alterations of speech and voice production were described primarily via perceptual coordinates. In this study, the spatial-temporal properties of syllable production were examined in 12 speakers, six of whom were healthy speakers and six with ataxia. The speaking task was designed to elicit six different prosodic conditions and four contrastive prosodic events. Distinct prosodic patterns were elicited by the examiner for cerebellar patients and healthy speakers. These utterances were digitally recorded and analysed acoustically and statistically. The healthy speakers showed statistically significant differences among all four prosodic contrasts. The normal model described by the prosodic contrasts provided a sensitive index of cerebellar pathology with quantitative acoustic analyses. A significant interaction between subject groups and prosodic conditions revealed a compromised prosody in cerebellar patients. Significant differences were found for durational parameters, F0 and formant frequencies. The cerebellar speakers demonstrated different patterns of syllable lengthening and syllable reduction from that of the healthy speakers.